2010
DOI: 10.1073/pnas.1005486107
|View full text |Cite
|
Sign up to set email alerts
|

Declining lymphoid progenitor fitness promotes aging-associated leukemogenesis

Abstract: Aging is associated with the functional decline of cells, tissues, and organs. At the same time, age is the single most important prognostic factor in the development of most human cancers, including chronic myelogenous and acute lymphoblastic leukemias initiated by Bcr-Abl oncogenic translocations. Prevailing paradigms attribute the association between aging and cancers to the accumulation of oncogenic mutations over time, because the accrual of oncogenic events is thought to be the rate-limiting step in init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 35 publications
8
73
0
Order By: Relevance
“…The aging-associated decreases in the expression of the key purine synthesis genes hypoxanthine-guanine phosphoribosyltransferase (Hprt) and guanine monophosphate synthase (Gmps) were confirmed using quantitative PCR (qPCR) analysis in sorted pro-B cell populations ( Figure 1B). IL-7 signaling decreases with age in B cell progenitors (16,37). Similar to previous reports (38), inhibiting IL-7R signaling by injecting mice with IL-7 neutralizing Abs (αIL-7) significantly decreased the expression of Pax5 in pro-B cells ( Figure 1C).…”
Section: Metabolic and Cell-cycle Defects Accompany Aging B Lymphopoisupporting
confidence: 75%
See 4 more Smart Citations
“…The aging-associated decreases in the expression of the key purine synthesis genes hypoxanthine-guanine phosphoribosyltransferase (Hprt) and guanine monophosphate synthase (Gmps) were confirmed using quantitative PCR (qPCR) analysis in sorted pro-B cell populations ( Figure 1B). IL-7 signaling decreases with age in B cell progenitors (16,37). Similar to previous reports (38), inhibiting IL-7R signaling by injecting mice with IL-7 neutralizing Abs (αIL-7) significantly decreased the expression of Pax5 in pro-B cells ( Figure 1C).…”
Section: Metabolic and Cell-cycle Defects Accompany Aging B Lymphopoisupporting
confidence: 75%
“…Thus, provision of the oncogenic drivers is insufficient to induce leukemias, as the leukemic potential of the oncogenic mutations is only fully realized in the aged hematopoietic context. Notably, we have previously shown that the differential ability of BCR-ABL to induce leukemias in young and old hematopoietic backgrounds does not require an intact adaptive immune system (16).…”
Section: V12mentioning
confidence: 99%
See 3 more Smart Citations